Study on Shear Behavior of Multi-Bolt Connectors for Prefabricated Steel–Concrete Composite Beams - Wang, Wei; Zhang, Xie-dong; Zhou, Xi-long; Wu, Lin; Zhu, Hao-jie (Frontiers in Materials, 2021)
Multi-bolt shear connectors (MBSCs), arranging bolts as a group in several rows, can be applied in prefabricated steel-concrete composite beams or bridges (SCCBs) to reduce construction time and meet the requirements of sustainable development. The mechanical behavior of bolt shear connectors has been broadly investigated in recent years, but they were mainly focused on the normal arrangement. The shear performance of MBSCs is not consistent with that of the same number of single bolts. In this paper, a 3D finite element model (FEM) was developed to investigate the multiple bolt effect and its mechanical performance. Material nonlinearities and the interactions among all components were included in the FEM. The accuracy and reliability of the proposed FEM were initially verified against the available push-out test results. The validated FEM further studied the load-slip relationship, shear capacity, and shear stiffness of the MBSCs. A parametric study was carried out to determine the effect of the bolt spacing, bolt row numbers, concrete strength, and the bolt diameter on the shear performance of MBSCs. Based on the extensive parametric analyses, design recommendations considering the multiple bolts effect for predicting the shear resistance of per bolt in multi-bolt connectors were proposed and verified.